Lithic arrowheads: Siliceous raw material sources and technology in Southern Portugal - Costa, Mafalda (2022)
This analysis focused on one hundred and fifteen lithic arrowheads recovered from the Zambujeiro and Mitra 2 dolmens, funerary monuments in Évora, Portugal. These were analyzed by noninvasive and minimally invasive analytical techniques, including handheld X‐ray fluorescence (hXRF), variable pressure scanning electron microscope coupled with energy dispersive X‐ray spectrometry (VP‐SEM‐EDS), and laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) to establish the sources of the raw materials used to manufacture these arrowheads and to compare and cluster different artefacts. The raw materials used in the manufacture of the arrowheads were found to be from different sources suggesting that long‐distance trade routes extending south, east and possibly west were in place in Southern Iberia during the Neolithic and Chalcolithic periods. Whether this difference is related to the availability of raw materials throughout time, different procurement strategies, or simply by choice, remains unknown. The trade routes associated with the Mitra 2 Dolmen also seem to have a greater range than those connected to the Zambujeiro Dolmen.